"asking with tears forgiveness": Weeping as 'Gentling' in Blake's Milton. Issue 2 (February 2014) - Lafford, Erin
Abstract In this article I wish to counter a critical perception of Blake as a 'hard' and unforgiving poet through a reading of his epic Milton as a conscious study in the nature of forgiveness. Specifically, I frame Blake's model of forgiveness as integral to his belief that every human has an inherent right and potential to participate in a divine body of imagination, in order to conduct a study of how Blake sees this as being achieved. Our divinity, and therefore our humanity in Blake's terms, is made manifest, not through hardness, supremacy and strength that allows us to overcome difficulties, but through softness and gentleness. Specifically, I draw on the theologian Stanley Hauerwas' notion of 'gentling' ("Christ's Gentle Man, " 2010) to define this softness, a term he develops from a reading of the beatitudes of Matthew's gospel to forward an understanding of the divine, not as strong, but as broken and mourning, to argue that Blake attempts to gentle and forgive fragmented individuals by presenting them with moments of weeping in his poetry, an action that calls the weeping figure into divinity through a forgiving process of meeting, of both the self and others. Alongside Hauerwas' notion of gentling, Martin Buber's I and Thou (1937) also offers a way of situating forgiveness in the difference between hard and soft relations, as this article illustrates. The absence of connection or 'meeting' in Buber's 'I–It' relationship, I argue, is founded on 'hardness', the 'I' seeing the other only as an object from which he or she is removed. The 'I–Thou' relationship, however, is gentling and mutual, expressive of Blake's vision of forgiveness and its importance within the divine human.